2012
DOI: 10.4103/0974-7753.111204
|View full text |Cite
|
Sign up to set email alerts
|

Hirsutism: A Clinico-investigative Study

Abstract: Background:Hirsutism is a common clinical condition characterized by presence of terminal hair at body sites under androgenic influence. Inspite of the significant worldwide prevalence of hirsutism, studies on hirsutism from India are not many.Objective:To assess the etiology of hirsutism and correlate its severity with underlying causes and various hormone levels.Materials and Methods:In this prospective study, 40 patients of hirsutism enrolled on first come basis were included. All patients underwent detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
6
7
1
Order By: Relevance
“…[18192021] Menstrual irregularities reported in 43% of our patients was also in agreement and disagreement with other studies. [1718192021] Contradictory to previous reports 80% of our patients were married with 26.3% having a history of infertility. [1820]…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[18192021] Menstrual irregularities reported in 43% of our patients was also in agreement and disagreement with other studies. [1718192021] Contradictory to previous reports 80% of our patients were married with 26.3% having a history of infertility. [1820]…”
Section: Discussionsupporting
confidence: 79%
“…[161718] The duration of hirsutism (>1 year) was both in agreement and disagreement with other studies. [17181920] The family history of hirsutism was present in 23% of our patients, and the family history ranged from 16% to 45% in different studies. [18192021] Menstrual irregularities reported in 43% of our patients was also in agreement and disagreement with other studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Chhabra et al . in their study found that 42.5% of women had a positive family history [8] while Ahmad et al found the positive family history only in 25.7% of cases [9]. Ghalib et al have observed that 24.1% of females with hirsutism had a positive family history [10].…”
Section: Discussionmentioning
confidence: 99%
“…The interest to acyl derivatives of sulfonylhydrazides is connected with a wide spectrum of their application: surfactants, antioxidants, curing agents, a basis of power supply sources in electronic engineering, fungicides, drugs [1][2][3].…”
mentioning
confidence: 99%